2016
DOI: 10.3389/fbioe.2016.00059
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes in Fish and Seafood Processing

Abstract: Enzymes have been used for the production and processing of fish and seafood for several centuries in an empirical manner. In recent decades, a growing trend toward a rational and controlled application of enzymes for such goals has emerged. Underlying such pattern are, among others, the increasingly wider array of enzyme activities and enzyme sources, improved enzyme formulations, and enhanced requirements for cost-effective and environmentally friendly processes. The better use of enzyme action in fish- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 126 publications
(160 reference statements)
1
33
0
Order By: Relevance
“…It also indicated that fish peptone of T. jarbua was not suitable for the growth media of E. cloacae and S. aureus. Bioactive compounds from fish protein hydrolysates could contain base, amino acid, endogenous enzymes, bacteria, and digestive protease [13]. The present study also showed that peptone from T. jarbua could become specific growth medium for bacteria.…”
Section: Microbiology Analysissupporting
confidence: 55%
“…It also indicated that fish peptone of T. jarbua was not suitable for the growth media of E. cloacae and S. aureus. Bioactive compounds from fish protein hydrolysates could contain base, amino acid, endogenous enzymes, bacteria, and digestive protease [13]. The present study also showed that peptone from T. jarbua could become specific growth medium for bacteria.…”
Section: Microbiology Analysissupporting
confidence: 55%
“…Fat in seafood can also be hydrolyzed by lipase or phospholipase (Aryee, Simpson, & Villalonga, ; Kaneniwa, Yokoyama, Murata, & Kuwahara, ). Hydrolysis of mono‐, di‐, and triglycerides to glycerol and fatty acids is induced by triacylglycerol acylhydrolases (EC 3.1.1.3) in the presence of water (Fernandes, ). FFAs liberated in seafood can readily undergo oxidation, which contributes to the formation of off‐odor, particularly fishy odor.…”
Section: Seafood Spoilagementioning
confidence: 99%
“…The reduction of TMAO to TMA and other basic volatiles by the action and metabolism of the endogenous or microbial enzymes increases the pH of stored seafood (Leelapongwattana et al, 2005;Leelapongwattana, Benjakul, Visessanguan, & Howell, 2008) Fat in seafood can also be hydrolyzed by lipase or phospholipase (Aryee, Simpson, & Villalonga, 2007;Kaneniwa, Yokoyama, Murata, & Kuwahara, 2004). Hydrolysis of mono-, di-, and triglycerides to glycerol and fatty acids is induced by triacylglycerol acylhydrolases (EC 3.1.1.3) in the presence of water (Fernandes, 2016). FFAs liberated in seafood can readily undergo oxidation, which contributes to the formation of off-odor, particularly fishy odor.…”
Section: Enzymatic Deterioration In Seafoodmentioning
confidence: 99%
“…In a very recent comprehensive review, it is reported that significant developments can be expected for enzyme applications in the fish and seafood industries [98] in the near future. …”
Section: Food Applicationsmentioning
confidence: 99%